Decision Support System for Determining the Best Store Location at PT. Sumber Alfaria Trijaya Using the Ahp (Analytical Hierarchy Process) Method - azlina Andriyani; Pristiwanto (INFOKUM, 2020)
DSS is designed to support all stages of decision making starting from identifying problems, selecting relevant data, determining the approach used in the decision-making process, to evaluating the selection. AHP is a decision support model developed by Thomas L. Saaty. This decision support model will describe a complex multi-factor or multi-criteria problem into a hierarchy, the hierarchy is defined as a representation of a complex problem in a multi-level structure where the first level is the goal, followed by the factor level, criteria, sub-criteria, and so on down to the last level of the alternatives. With a hierarchy, a complex problem can be broken down into groups which are then arranged into a hierarchical form so that the problem will appear more structured and systematic, in order to compete with several similar companies, PT. Sumber Alfaria Trijaya must be able to provide optimal service not only for consumers, but also for staff and employees so that they can work optimally. To be able to answer these challenges, the technology used must be able to balance the need for this. Because this company is engaged in retail, problems will arise both in the store, in the warehouse or in the system used.